Effect of Text Messaging on Food Consumption Behavior and Change of Hemoglobin Level in Pregnant Women with Iron Deficiency Anemia - Pintawong, Wilailuk; Yusamran, Chaweewan; Thananowan, Nanthana (Journal of The Royal Thai Army Nurses, 2020)
This quasi-experimental research aimed at determining effect of text messaging on food consumption behaviour and change of hemoglobin level in pregnant women with iron deficiency anemia visiting the antenatal care unit at Vajira Hospital, Bangkok. Sample was comprised of 40 pregnant women with iron deficiency anemia. Divided into experimental group and control group, 20 persons per group. They were match-paired by age and parity. The control group received routine care, while the experimental group received routine care and the text messages. Hemoglobin was measured 2 weeks after the intervention. Data were analyzed by frequency, percentage, mean, standard deviation, Chi-Square test, and t-test. The findings reveal that the experimental group had significantly higher mean difference scores of food consumption behaviour than the control group (t = 6.96, p < .05).Mean hemoglobin in the experimental group was statistically and significantly higher than the control group (t = 2.54, p < .05).The change of hemoglobin level in the experimental group was statistically higher than the control group (t = 3.35, p < .05). The results suggest that the text messaging is effective in reducing the iron deficiency anemia in pregnant women.